Dampak Bermain Game Online bagi Peserta Didik Sekolah Dasar - Muhamad Rendi Septianto; Suyitno Suyitno; Moh. Aniq Khairul Basyar (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this study was to determine the impacts of playing online games for elementary school students, especially on the negative impacts. This research is qualitative research. The approach used in this study is a library research approach and secondary source data. The source of this research is based on scientific journals. The research subjects are from several journals or articles and thesis. In this study, researchers used literature data collection techniques and documentation methods. Based on the results of the analysis and study of the literature, which amounted to six articles, it can be concluded that learning is the most affected by playing online games with a percentage of 30.7%. On average, students are more interested in playing online games than in learning. The impact of playing online games that causes students to become addicted is 23.07%. The impact of playing online games on social has a percentage of 15.3%. The impact on the character of students has a percentage of 15.3%. The impact of playing online games on health has a percentage of 7.7%. And the impact of playing online games on lifestyle is 7.7%.